Whole-body wear-resistant special granite ceramic tile with spot crystal effect and preparation method thereof
By using polycrystalline wear-resistant blank formula and high porphyry permeable formula, combined with digital spraying and whole-body fabric technology, the existing porphyry granite ceramic tiles have been solved, and high hardness has been achieved The formation of wear-resistant decorative layers and the perfect imitation of porcine granite texture are suitable for high-end decoration in public places.
Patent Information
- Application Number
- CN202411486783.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing porcine granite ceramic tiles have a single texture pattern, which cannot completely imitate the crystalline granite texture effect of natural granite. At the same time, the wear resistance of its glaze finish is insufficient, resulting in easy wear and tear when applied in public places and loss of surface pattern texture.
Using polycrystalline wear-resistant blank formula and high pomegranate formula, combined with digital spraying technology and full-body fabric technology, after high temperature firing, a high hardness wear-resistant decorative layer with a thickness of 0.5mm to 1.0mm is formed, perfectly It presents the texture effect of porcine granite and improves the decorative durability and wear resistance.
The formation of a high-hard wear-resistant decorative layer is achieved, perfectly imitating the rich texture effect of porphyrycrystal granite, and at the same time improving the wear resistance and durability of the product, making it suitable for a wide range of public applications.
Smart Images

Figure CN119409484A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles, and particularly relates to a full-body wear-resistant special granite ceramic tile with phenocryst effect and a preparation method thereof. Background Art
[0002] Phenocryst granite, also known as crystalline granite, has other silicate crystal grains of different sizes scattered in the granite background. These silicate crystals exist in a transparent or translucent state, adding a unique aesthetic to the stone. The grains of minerals inside it actually become the patterns of the stone. These patterns are naturally formed, forming a strong contrast with the granite pattern, further enriching the visual effect of the stone texture. Common colors include gray, black, red, and white. There are white phenocrysts in black stone, gray phenocrysts in white stone, and black and white phenocrysts in red stone. Phenocryst granite has obvious texture and smooth surface. It is usually used for indoor walls, floors, columns, countertops, etc. It is one of the main building materials for high-end public places.
[0003] As a non-renewable resource, phenocryst granite has begun to show a trend of resource depletion over time. In order to protect mineral resources, the country has strictly controlled the mining of granite, and this measure has had a huge impact on the outdoor building materials market. As a result, people are eager to find a building material that can replace granite. At this time, granite tiles came into being. Granite tiles are both beautiful and exquisite, practical and efficient. They can be widely used in high-end building decoration projects such as villas, gardens, and communities, as well as public scenes with large traffic such as leisure squares, municipal projects, landscaping, subways and railway stations. At the same time, during the use process, there will be no qualitative changes or weathering of stone materials.
[0004] However, the imitation porphyroblastic granite products prepared by using fabric or granulation mixing and other process methods generally have the problem of single texture pattern, and cannot completely imitate the porphyroblastic texture effect of porphyroblastic granite stone. At present, the best imitation of the texture effect of porphyroblastic granite stone is the glazed ceramic products produced by decorative printing technology such as inkjet or screen, but the decorative pattern layer of conventional glazed tiles is generally within 0.1mm, and a layer of transparent glass glaze with a thickness of about 0.2mm needs to be covered on its surface during use. The hardness of the glass glaze layer is relatively poor, and the decorative layer underneath is easily worn during use, resulting in the loss of surface pattern texture. It can be seen that there is a fatal flaw in the application of granite glazed ceramic tiles in public places, and the wear resistance of its glazed surface is not enough, and most of them can only be used as ordinary floor tiles. Therefore, the production technology of existing imitation porphyroblastic granite ceramic tiles needs to be improved and developed. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the technical problem to be solved by the present invention is to provide a kind of high-hardness and wear-resistant decorative layer with a thickness of 0.5mm to 1.0mm obtained by combining a polycrystalline phase green body formula with a highly transparent porphyroblastic formula, combining the application of digital spraying technology and full-body fabric technology, after high-temperature firing, which can not only perfectly present the rich texture effect of porphyroblastic granite stone, but also have super long decorative durability and wear resistance, and can be widely used in public places. Wear-resistant special granite ceramic tiles with porphyroblastic effects and their preparation method.
[0006] The technical solution of the present invention is a method for preparing the wear-resistant special granite ceramic tile with phenocryst effect, which is special in that it includes the following steps:
[0007] ⑴ Preparation of polycrystalline wear-resistant matrix green body formula slurry: The raw materials in the polycrystalline wear-resistant matrix green body formula are mixed and ball-milled according to the proportion, and the polycrystalline wear-resistant green body formula slurry is obtained and then sent to the transfer slurry pool for storage and aging for standby use;
[0008] (2) Preparation of high-transmittance phenocryst blank formula slurry: The raw materials in the high-transmittance phenocryst blank formula are mixed and ball-milled according to the proportion, and the high-transmittance phenocryst blank formula slurry is sent to the transfer slurry pool for storage and aging for later use;
[0009] ⑶ Preparation of powders of different colors: according to the requirements of the texture pattern design, add a set ratio of ceramic colorant or emulsifier to the polycrystalline wear-resistant green body formula slurry in step ⑴ and the high-transparency porphyroblast green body formula slurry in step ⑵, stir evenly and send to a spray drying tower for powdering to obtain color powder and store it for aging for later use;
[0010] (4) Preparation of granular materials of different colors: Part of the color powder of step (3) is granulated by a granulating device to obtain granular materials of different colors;
[0011] (5) Preparation of mixed powder: uniformly mix the color powder of step (3) and the color granular material of step (4) according to the designed ratio to obtain a mixed powder for use;
[0012] (6) Whole-body fabrication: The mixed powder material in step (5) is arranged in texture according to the design parameters through the whole-body fabrication forming system to obtain a blank layer with a phenocryst granite texture;
[0013] (7) Pressing and molding: feeding the blank layer of step (6) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0014] ⑻ Drying: The formed wear-resistant body layer is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa;
[0015] ⑼ Water spraying: spray water on the surface of the wear-resistant blank in step ⑻ to wet it;
[0016] ⑽Preparation of color slurry: Based on the formula of the polycrystalline wear-resistant matrix body in step ⑴ and the formula of the high-transparency porphyroblast body in step ⑵, ceramic colorant and kaolin are introduced, and the color slurry is obtained through calcination, grinding and spray drying.
[0017] ⑾Spraying decoration: on the wetted surface of the blank, use the color slurry in step ⑽ to perform digital spraying decoration according to the designed pattern to form a decorative wear-resistant layer;
[0018] ⑿ Drying of decorative wear-resistant layer: drying temperature is 100-200℃, drying time is 3-8min;
[0019] ⒀High temperature firing: sending the ceramic body of step ⑿ into a roller kiln for firing;
[0020] ⒁Processing: The fired semi-finished products are polished or not polished and ground, and finally the wear-resistant special granite ceramic finished tiles with polished, natural or special-shaped surfaces are obtained.
[0021] As preferred: the polycrystalline wear-resistant blank formulation in the step (1) is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, blank reinforcing agent 0 to 1%, and debonding agent 1 to 3%;
[0022] The multi-crystalline wear-resistant blank formulation is composed of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 1-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%;
[0023] In the step (1), the processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm.
[0024] As a preference: the fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100%, a Fe2O3 content of 0-1%, and a particle size D50 < 3 μm;
[0025] The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements 0-1wt%, ignition loss 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm; the trace elements include rubidium, gallium, strontium, cadmium, and nickel;
[0026] The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm;
[0027] The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96%, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.
[0028] As a preference, the high-transparency phenocryst blank in step (2) is composed of the following raw material components by weight: 8% to 15% ultra-white ball clay, 8% to 15% ultra-white kaolin, 0% to 5% ultra-white burned talc, 3% to 6% high-white bentonite, 15% to 25% high-white sodium potassium stone, 10% to 20% glass powder, 10% to 20% ultra-white lithium tailings powder, 10% to 20% barium carbonate, 0% to 1% blank reinforcing agent, and 1% to 3% debonding agent;
[0029] The formula of the high-transparent phenocryst green body is composed of the following chemical components by weight percentage: Al2O3 15-20wt%, SiO2 60-70wt%, K2O 1-3wt%, Fe2O3 0-0.5wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, BaO 7-16wt%, and ignition loss 0-8wt%;
[0030] In step (2), the whiteness of the high-transmittance porphyroblast blank formula is controlled to be 70-80%, the transmittance is controlled to be 10-20%, the high-transmittance porphyroblast blank formula is processed by wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm;
[0031] The raw materials used in the high-transparency porphyroblastic body formula of step (2) are ultra-white ball clay, ultra-white kaolin, ultra-white burned talc, ultra-white bentonite, ultra-white lithium tailings powder, and high-white potassium sodium stone, which are obtained by removing iron from ball clay, high-white kaolin, burned talc, bentonite, potassium sodium stone powder, and finely ground lithium tailings. The raw materials are deironed 1 to 5 times, and the whiteness is controlled to be 70 to 80%.
[0032] Preferably, the color powder in step (3) is composed of the following components by weight percentage: 0-100wt% of polycrystalline wear-resistant green body formula slurry, 0-100wt% of high-transparency porphyroblast green body formula slurry, 0-5wt% of ceramic colorant, and 0-10wt% of opacifier; the color powder is provided with 2-10 different types of colors;
[0033] The ceramic colorant in step (3) is selected from the following:
[0034] The invention is composed of the following components by weight percentage: cobalt blue: 0-100wt%, manganese red: 0-100wt%, apple green: 0-100wt%, chrome green: 0-100wt%, orange yellow: 0-100wt%, praseodymium yellow: 0-100wt%, cobalt black: 0-100wt%;
[0035] The composition is composed of the following components by weight percentage: cobalt blue: 0-100wt%, vanadium zirconium blue: 0-100wt%, brown: 0-100wt%, package red: 0-100wt%, orange: 0-100wt%, package yellow: 0-100wt%, black: 0-100wt%, green: 0-100wt%;
[0036] The opacifier in step (3) is composed of the following components by weight percentage: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%;
[0037] Step (3) The spray drying tower adopts a pressure spray drying system, the spray drying system uses a nozzle sheet combination with an aperture of 1.5 mm to 2.0 mm, and the atomization pressure is 1.8 MPa to 2.6 MPa. The particle grading of the obtained powder is that the particles on the 20 mesh sieve account for less than 6%, the particles between 20 mesh and 40 mesh account for 20% to 25%, the particles between 40 mesh and 60 mesh account for 40% to 45%, the particles between 60 mesh and 80 mesh account for 15% to 20%, and the particles below 80 mesh account for less than 3%, and the specific gravity of the powder is 0.85 to 0.95 g / cm 3 , the moisture content is controlled at 6-8%, and the angle of repose is controlled at 33°-38°.
[0038] As a preferred embodiment: the granulation equipment in step (4) comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, which is composed of a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder in step (3) on the surface of the conveyor belt in multiple layers according to the design parameters, and the scraping device is used to scrape the powder at a fixed height according to the particle thickness requirement, and then the pressure roller is used to press the powder into a block, and finally the powder is transported to the cutter to be processed into color granular materials of different colors, sizes and shapes for storage and standby; the color granular materials are provided with 2 to 6 kinds, and the particle size is controlled to be 3 to 20 mm: the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥0.1 Mpa, and the volume density is controlled to be ≥1.0 g / cm 3 ; In step ⑸, the mixed powder is set to 2 to 6 types, and is composed of the following components by weight percentage: color powder: 0 to 100wt%, color granular material: 0 to 100wt%.
[0039] As a preferred embodiment: the whole body fabric forming system described in step (6) comprises a whole body fabric platform, a pressing and forming platform, and a conveying mechanism; the whole body fabric platform is composed of a fabric mechanism, a transition belt arranged at the bottom of the fabric mechanism, a transition hopper arranged at a position where the transition belt travels at a terminal lower than the transition belt, a grid connected to the bottom of the transition hopper, a movable feeding hopper arranged longitudinally above the conveying mechanism on the side of the pressing and forming platform, and a transfer feeding hopper; the fabric mechanism is designed in multiple groups and arranged at the top of the whole body fabric platform;
[0040] The material distribution mechanism forms a blank layer after the material distribution is completed according to the designed texture pattern. The blank layer is transferred to the transition hopper by the transition belt, and is fixed by the grid and then sent to the mold cavity in the pressing and forming platform arranged at the tail end of the whole material distribution platform through the conveying mechanism. The material is fed by the movable feeding hopper and scraped flat, and then pressed and formed to obtain a wear-resistant blank layer.
[0041] In step (6), the blank layer is formed by a whole-body fabric forming system to form a granite pattern texture that is consistent from bottom to top, and its thickness can be controlled to be 18 mm to 80 mm.
[0042] As a preferred embodiment: in step ⑺, the pressing pressure is > 40MPa / cm 2 , the thickness of the wear-resistant green body layer is controlled to be 9mm-40mm; the drying time in step ⑻ is 50-120 minutes; the residual moisture of the green body after drying is ≤0.5%; the color slurry in step ⑽ is composed of the following components by weight percentage: 95-100% base slurry, 0-5% ceramic colorant, prepared by weight percentage, and ground into slurry using a wet ball milling process; the specific gravity of the color slurry is controlled to be 1.75±0.5g / cm 3, 40° viscosity is 60~150mpa.s, D50 particle size is controlled to be 10μm~15μm;
[0043] The basic slurry is composed of the following components by weight percentage: light-burned wear-resistant material: 0-90wt%, light-burned high-permeability material: 0-90wt%, kaolin: 8-20wt%, CMC: 0.2-1.0wt%, trimer: 0.5-1.0wt%, defoamer: 0.2-1.0wt%;
[0044] The formula compositions of the lightly fired wear-resistant material and the lightly fired high-permeability material are respectively consistent with the formula of the polycrystalline wear-resistant blank in step (1) and the formula of the high-transparency porphyroblast blank in step (2), except that light firing is required; the light firing is to prepare the formula according to weight percentage, and then ball-mill it into slurry according to a wet process, wherein the slurry has a moisture content of 35-40%, a viscosity of 40-80 mpa.s at 40°, and a D50 particle size of 3μm-6μm; spray-dry the ball-milled slurry to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain the lightly fired wear-resistant material and the lightly fired high-permeability material.
[0045] As a preferred embodiment: the decorative wear-resistant layer in step ⑾ is formed by CNC spraying process, using a variety of different color slurries for decorative printing according to the designed pattern texture, the digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, the pattern is narrowed by 0.2mm to 0.4mm, and the thickness of the decorative wear-resistant layer is 0 to 1mm;
[0046] The digital spraying process in step ⑾ is a process of directly controlling the printing by using digital information, which can realize the printing of 4 to 10 different color slurries at the same time, and the printing amount per square meter is controlled to be 0 to 1800g;
[0047] The high temperature firing described in step (9) is performed at a firing temperature of 1180-1250°C for 60-120 minutes. The water absorption rate of the fired product is ≤0.5%, and the Ra value of the product out of the kiln refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3 μm.
[0048] The processing in step ⒁ includes two situations. The first situation is to directly grind the edge of the product after sintering in step ⒀; the second situation is to first polish the product obtained in step ⒀ and then grind the edge;
[0049] The polishing is the polishing of the wear-resistant surface: the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
[0050] Another technical solution of the present invention is the wear-resistant special granite ceramic tile with phenocryst effect, which is special in that it is prepared by any of the preparation methods described above.
[0051] The third technical solution of the present invention is the polycrystalline wear-resistant body of the wear-resistant special granite ceramic tile with phenocryst effect, which is special in that the polycrystalline wear-resistant body formula is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, body reinforcing agent 0 to 1%, and debonding agent 1 to 3%;
[0052] The multi-crystalline wear-resistant blank formula consists of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 1-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%.
[0053] The fourth technical solution of the present invention is the high-transparent porphyroblastic body of the wear-resistant special granite ceramic tile with porphyroblastic effect, which is special in that the formula of the high-transparent porphyroblastic body is composed of the following raw material components by weight percentage: ultra-white ball clay 8% to 15%, ultra-white kaolin 8% to 15%, ultra-white burned talc 0% to 5%, high-white bentonite 3 to 6%, high-white potassium sodium stone 15 to 25%, glass powder 10 to 20%, ultra-white lithium tailings powder 10% to 20%, barium carbonate 10% to 20%, body reinforcing agent 0 to 1%, and debonding agent 1 to 3%;
[0054] The formula of the high-transparent phenocryst green body consists of the following chemical components by weight percentage: Al2O3 15-20wt%, SiO2 60-70wt%, K2O 1-3wt%, Fe2O3 0-0.5wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, BaO 7-16wt%, and ignition loss 0-8wt%.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] ⑴ The present invention provides a wear-resistant special granite ceramic tile with phenocryst effect. The phenocryst granite ceramic tile uses a polycrystalline wear-resistant green body formula as a matrix material. After high-temperature firing, it can react to generate a variety of high-hardness wear-resistant crystals including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, calcium feldspar, cordierite, etc. These high-hardness wear-resistant crystals are not only of many types, but also of high content, thereby improving the wear resistance of the product.
[0057] ⑵ The polycrystalline wear-resistant blank formula of the present invention has the following advantages: ① The formula introduces a large amount of fine corundum powder. Through the finely processed corundum powder, on the one hand, the aluminum content of the formula can be increased, and at the same time, the reaction activity of the blank in the sintering process can be improved, thereby promoting the formation of wear-resistant crystals such as mullite, feldspar, and corundum. ② The formula grinds lithium tailings finely. In addition to conventional elements such as silicon, aluminum, potassium, and sodium, lithium tailings also contain special elements such as rubidium, gallium, strontium, cadmium, and nickel, and have a high SiO2 content. Fine grinding can promote the fluxing effect of trace elements, while improving the reaction activity of SiO2 and promoting the growth of quartz crystal phase. The introduction of lithium and the generation of quartz crystals can improve the wear resistance of granite ceramic tiles. ③ The formula introduces ultrafine zirconium silicate and titanium dioxide powder, which can promote the formation of zircon and rutile crystals. Zircon and rutile crystals are both high-hardness substances, which can better improve the wear resistance of the product.
[0058] ⑶ In order to achieve the effect of crystal porphyry in granite, the present invention has developed a high-transparency porphyry formula with a whiteness of more than 70% and a transmittance of more than 10%. A large amount of barium carbonate and potassium sodium stone powder are introduced into the green body formula. After high-temperature sintering, it can react to produce more potassium sodium barium orthoclase, sanuclear feldspar and other crystals with a transmittance close to that of glass and amorphous phase materials. The raw material quality is further improved through multiple iron removal processes, thereby obtaining a crystal porphyry material with high whiteness and transmittance;
[0059] (4) The present invention provides a whole-body fabric production process and technology. By combining particle preparation, powder mixing, whole-body fabric and other technical processes, the preparation of whole-body wear-resistant special ceramic tiles is completed, achieving a whole-body decorative effect with consistent product pattern texture inside and outside.
[0060] ⑸ The present invention provides a method for preparing a digital spray decorative wear-resistant layer. The method promotes the growth of wear-resistant crystals by pre-processing the formulated materials by light firing, so that the product reaches or even exceeds the surface hardness and wear resistance of natural granite. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a diagram showing the phase detection results of the polycrystalline wear-resistant blank of Example 1 of the present invention;
[0062] Figure 2 This is a diagram showing the physical phase detection results of the high-transmittance phenocryst material of Example 1 of the present invention;
[0063] Figure 3 This is a graph showing the physical phase detection results of the ceramic tile of Comparative Example 1;
[0064] Figure 4 This is the result of phase detection of ceramic bricks in Example 2
[0065] Figure 5 This is the effect diagram of the wear-resistant special phenocrystal granite ceramic tile of the present invention;
[0066] Figure 6 It is a schematic diagram of the whole body cloth forming system of the present invention.
[0067] Main component symbols:
[0068] Whole body fabric platform 1 Fabric mechanism 11 Transition belt 12 Transition hopper 13 Grille 14 Transfer hopper 15 Movable feeding hopper 16 Pressing molding platform 2 Cavity 21 Conveying mechanism 3 DETAILED DESCRIPTION
[0069] The present invention will be further described in detail below in conjunction with embodiments:
[0070] Example 1
[0071] The wear-resistant special granite ceramic tile with phenocryst effect described in this embodiment mainly includes two parts: a wear-resistant body layer and a decorative wear-resistant layer. The main production process technology route is as follows:
[0072] ⑴ Preparation of polycrystalline wear-resistant matrix body formula slurry: The raw materials in the body formula are mixed and ball-milled according to the proportion, and the polycrystalline wear-resistant body formula slurry is sent to the transfer slurry pool for storage and aging for later use;
[0073] The polycrystalline wear-resistant green body formula is composed of the following raw material components by weight: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, green body reinforcing agent 0.35%, debonding agent 1.1%;
[0074] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0075] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0076] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.4%, a Fe2O3 content of 0.6%, and a particle size D50 of 1.86 μm;
[0077] The chemical composition of the finely ground lithium tailings is composed of Al2O3 17.83 wt%, SiO2 69.11 wt%, K2O 3.50 wt%, Fe2O3 0.68 wt%, Na2O 3.45 wt%, CaO 0.84 wt%, MgO 0.42 wt%, Li2O 0.41 wt%, trace elements: 0.18 wt%, and ignition loss 3.58 wt% by weight.
[0078] Trace elements include special elements such as rubidium, gallium, strontium, cadmium, nickel, etc. The particle size D50 of finely ground lithium tailings is 5.4μm;
[0079] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0080] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, 105° volatile matter of 0.3%, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm.
[0081] (2) Preparation of high-transparency phenocryst green body formula slurry: The raw materials in the green body formula are mixed and ball-milled according to the proportion, and the high-transparency phenocryst green body formula slurry is obtained and then sent to the transfer slurry pool for storage and aging for later use;
[0082] The high-transparency phenocryst green body formula is composed of the following raw material components by weight percentage: 12% super white ball clay, 12% super white kaolin, 3% super white calcined talc, 4% high white bentonite, 20% high white sodium potassium stone, 15% glass powder, 17.3% super white lithium tailing powder, 15% barium carbonate, 0.6% green body reinforcing agent, and 1.1% debonding agent;
[0083] The high-transparency phenocryst blank formula consists of the following chemical components by weight: Al2O3 16.12 wt%, SiO2 57.82 wt%, K2O 1.78 wt%, Fe2O3 0.14 wt%, Na2O 3.97 wt%, CaO 0.25 wt%, MgO 1.25 wt%, BaO 11.69 wt%, and ignition loss 6.98 wt%;
[0084] The whiteness of the high-transmittance porphyroblast green body formula is 76%, and the transmittance is controlled to be 16.3%. The high-transmittance porphyroblast green body formula is processed by wet ball milling process, and the median diameter D50 of the mud is 9.3 μm.
[0085] The ball clay, high white kaolin, burned talc, bentonite, potassium sodium stone powder and finely ground lithium tailings are subjected to an iron removal process for three times to obtain raw materials of ultra-white ball clay with a whiteness of 72%; ultra-white kaolin with a whiteness of 74%; burned talc with a whiteness of 77%; ultra-white bentonite with a whiteness of 73%; ultra-white potassium sodium stone powder with a whiteness of 79% and ultra-white lithium tailings powder with a whiteness of 81%.
[0086] ⑶ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of ceramic colorant or emulsifier is added to the polycrystalline wear-resistant green body formula of step ⑴ and the high-transparency porphyroblast green body formula slurry of step ⑵, and after being stirred evenly, it is sent to a spray drying tower for powdering to obtain colored powder and stored for aging for later use;
[0087] The color powder is set to 8 kinds, and the specific settings are as follows:
[0088] The white powder is composed of the following components by weight percentage: 90wt% of polycrystalline wear-resistant blank formula slurry and 10wt% of emulsifier; wherein the emulsifier is composed of the following components by weight percentage: 20wt% of zirconium dioxide, 55wt% of zirconium silicate and 25wt% of titanium dioxide;
[0089] The light apricot color powder is composed of the following components by weight percentage: 100wt% of high-transparency phenocryst blank formula slurry;
[0090] The gray powder is composed of the following components by weight percentage: 99.7wt% of polycrystalline wear-resistant blank formula slurry, 0.2wt% of cobalt black material, and 0.1wt% of orange material;
[0091] The light green powder is composed of the following components by weight percentage: 99.8wt% of high-transparent phenocryst blank formula mud, 0.18wt% of apple green material, and 0.02wt% of chrome green material;
[0092] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry 98.8wt%, cobalt black material 1.1wt%, manganese red material 0.1wt%;
[0093] The brown powder is composed of the following components by weight percentage: 97.3wt% of polycrystalline wear-resistant blank formula slurry, 0.4wt% of cobalt black material, 0.7wt% of praseodymium yellow material, and 1.6wt% of manganese red material;
[0094] The light yellow powder is composed of the following components by weight percentage: 99.4wt% of high-transparent phenocryst blank formula mud, 0.4wt% of orange material, and 0.2wt% of praseodymium yellow material;
[0095] The red color powder is composed of the following components by weight percentage: 98.4wt% of polycrystalline wear-resistant blank formula slurry, 1.3wt% of manganese red material, and 0.3wt% of praseodymium yellow material;
[0096] The spray drying tower adopts a pressure spray drying system, which uses a nozzle plate with an aperture of 1.8 mm and an atomization pressure of 2.2 MPa. The particle size distribution of the obtained powder is as follows: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°.
[0097] (4) Preparation of granular materials of different colors: The color powder of step (3) is granulated by a granulating device to obtain granular materials of different colors;
[0098] The color particle materials are provided in 5 kinds, specifically white particles, black particles, brown particles, light apricot particles, and light yellow particles;
[0099] The granulation equipment comprises five parts, namely, a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and can prepare particles with various effects, colors, thicknesses and specifications. The granulation equipment comprises a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads a total of five different color powders, namely, the white powder, the black powder, the brown powder, the light apricot powder and the light yellow powder in step (3) on the surface of the conveyor belt in multiple layers according to design parameters, and the scraping device scrapes the powder at a fixed height according to the particle thickness requirement, and then presses the powder into blocks by the pressure roller, and finally conveys the powder to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage.
[0100] The color particle material has a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a volume density of 1.61 g / cm 3 .
[0101] (5) Preparation of mixed powder: uniformly mix the color powder of step (3) and the color granular material of step (4) according to the designed ratio to obtain a mixed powder for use;
[0102] The mixed powder is provided in 4 types according to the design requirements; specifically,
[0103] A mixed powder is composed of the following components by weight percentage: 10wt% white particles, 5wt% black particles, 30wt% light apricot powder, and 55wt% gray powder;
[0104] Mixed powder B is composed of the following components by weight percentage: 8wt% brown particles, 15wt% light yellow particles, 5wt% white particles, 3wt% black powder, and 69wt% gray powder;
[0105] Mixed powder C is composed of the following components by weight percentage: 5wt% brown particles, 20wt% light apricot particles, 10wt% white particles, 15wt% red powder, 40wt% grey powder, and 10wt% light green powder;
[0106] The D mixed powder is composed of the following components by weight percentage: 15wt% of light yellow powder, 35wt% of light apricot powder, 3wt% of black powder, and 47wt% of gray powder.
[0107] (6) Whole-body fabrication: The mixed powder material in step (5) is arranged in texture according to the design parameters through the whole-body fabrication forming system to obtain a blank layer with a phenocryst granite texture;
[0108] See also Figure 6 As shown, the whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform is composed of a fabric mechanism 11, a transition belt 12, a transition hopper 13, a grille 14, a transfer feeding hopper 15, and a movable feeding hopper 16. The fabric mechanism 11 is designed with 6 groups, which are arranged at the top of the whole body fabric platform 1. The fabric mechanism 11 forms a blank layer after fabricating according to the designed texture pattern. The blank layer is conveyed to the transition hopper 13 by the transition belt 12 and fixed by the grille 14, and then conveyed to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole body fabric platform 1 through the conveying mechanism 3. The movable feeding hopper 16 feeds the material and scrapes it flat, and then presses and forms the wear-resistant blank layer;
[0109] The blank layer is formed by a whole body cloth forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm.
[0110] (7) Pressing and molding: feeding the blank layer of step (6) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0111] The pressing pressure of the pressing molding is 45MPa / cm 3 The wear-resistant green body layer has a thickness of 20 mm.
[0112] ⑻ Drying: The formed wear-resistant body layer is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0113] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0114] ⑼ Water spraying: spray water on the surface of the wear-resistant blank in step ⑻ to wet it;
[0115] ⑽Preparation of color slurry: Based on the formula of the polycrystalline wear-resistant matrix body in step ⑴ and the formula of the high-transparency porphyroblast body in step ⑵, introduce pigments and raw materials such as ceramic colorants and kaolin, and obtain color slurry through calcination, grinding, spray drying and other processing techniques;
[0116] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is 1.75g / cm 3 , 40° viscosity is 60mpa.s, D50 particle size is controlled to 12μm;
[0117] The color paste is provided in 8 types according to the design requirements, specifically including:
[0118] The color paste 1 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of cobalt blue colorant;
[0119] Color slurry 2 is composed of the following components by weight percentage: wear-resistant base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0120] Color slurry 3 is composed of the following components by weight percentage: wear-resistant base slurry 98wt%, brown colorant 2wt%;
[0121] The color paste 4 is composed of the following components by weight: 98wt% of high-transparency base paste and 2wt% of wrapped red material;
[0122] The color slurry 5 weight percent is composed of the following components: wear-resistant base slurry 97wt%, orange color material 3wt%;
[0123] The color paste 6 weight percent is composed of the following components: 97wt% of high-transparency base paste, 3wt% of wrapped yellow material;
[0124] The color paste 7 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of black colorant;
[0125] The color paste 8 is composed of the following components by weight percentage: 98wt% of high-transmittance paste and 2wt% of green colorant;
[0126] The wear-resistant base slurry is composed of the following components by weight percentage: 89.2% of light-burned wear-resistant material, 9.52% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0127] The formula composition of the lightly fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank in step (1), except that a lightly fired process is required; the lightly fired process is to prepare the formula according to the weight percentage, and then ball-mill it into a slurry according to a wet process, wherein the slurry has a moisture content of 36%, a viscosity of 60 mpa.s at 40°, and a D50 particle size of 4 μm; the ball-milled slurry is spray-dried to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material, and fired at a temperature of 1080° C. to obtain the lightly fired wear-resistant material;
[0128] The high-permeability base slurry is composed of the following components by weight percentage: 89.2% of light-burned high-permeability material, 9.52% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0129] The formula composition of the lightly fired high-permeability material is consistent with the formula of the high-permeability phenocryst blank in step (2), except that it needs to be lightly fired; the lightly fired processing is to prepare the formula according to the weight percentage, and then ball-mill it into a slurry according to the wet process, the slurry has a moisture content of 36%, a viscosity of 60mpa.s at 40°, and a D50 particle size of 4μm; spray-dry the ball-milled slurry to obtain a powder, and put the obtained powder into a sagger made of refractory material, and fire it at a temperature of 1050°C to obtain the lightly fired high-permeability material;
[0130] ⑾Spraying decoration: on the wetted surface of the blank, use the color slurry in step ⑽ to perform digital spraying decoration according to the designed pattern to form a decorative wear-resistant layer;
[0131] The decorative wear-resistant layer is formed by decorative spraying of 8 different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2mm. The thickness of the decorative wear-resistant layer is 0.8mm.
[0132] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0133] ⑿ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer of step ⑾ at a drying temperature of 150° C. for 8 minutes;
[0134] ⒀High temperature firing: sending the ceramic body of step ⑿ into a roller kiln for firing;
[0135] The high temperature firing is performed at a temperature of 1220°C for 75 minutes. The water absorption rate of the product after firing is 0.06%, and the Ra value of the product out of the kiln is 1.72 μm.
[0136] ⒁Processing: Polish and grind the edges of the fired semi-finished products to finally obtain polished, wear-resistant special granite ceramic finished tiles.
[0137] The processing is specifically to polish the product obtained in step ⒀ first and then grind the edges, wherein the polishing is polishing of the decorative wear-resistant surface; the polishing process parameters are: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive blocks are matched as follows: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and Ra value of the product after polishing is 0.052μm.
[0138] Comparative Example 1
[0139] The whole body wear-resistant special granite ceramic tile with phenocryst effect, the body formula is composed of the following components by weight percentage (common body formula): 35# stone powder 20%, super white washed mud 28%, potassium sodium stone powder 24%, water abrasive 10%, super plastic soil 3%, talcum particles 5%, common mud paste 8.25%, body reinforcing agent 0.45%, degumming agent 1.3%;
[0140] The difference between Comparative Example 1 and Example 1 is that the polycrystalline wear-resistant green body formula of Example 1 is replaced with a common green body formula. The preparation method of Comparative Example 1 is the same as that of Example 1.
[0141] Specifically, the methods of Example 1 and Comparative Example 1 were used to prepare the wear-resistant special granite ceramic tiles, and the obtained ceramic tiles and polished natural granite were tested for the wear depth, flexural strength, water absorption, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 1 below:
[0142] Table 1 Example 1, Comparative Example 1 and natural granite (polished surface)
[0143]
[0144] The test results of Example 1, Comparative Example 1 and polished natural granite show that when the polycrystalline wear-resistant body formula of the present invention is replaced with a common body formula, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic plate will be significantly reduced. Figure 1 and Figure 2 The physical phase detection results show that the use of a multi-crystalline wear-resistant green body formula generates more crystal phases than an ordinary green body formula, including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite and other high-hardness wear-resistant crystals. Not only are there many types of crystal phases, but also the content is high. Therefore, the wear resistance of the granite ceramic prepared in Example 1 is significantly higher than that of Comparative Example 1 and natural granite.
[0145] Comparative Example 2
[0146] The wear-resistant special granite ceramic tile with phenocryst effect mainly includes two parts: wear-resistant body layer and decorative wear-resistant layer. Its main production process technology route is as follows:
[0147] ⑴ Preparation of polycrystalline wear-resistant matrix body formula slurry: The raw materials in the body formula are mixed and ball-milled according to the proportion, and the polycrystalline wear-resistant body formula slurry is sent to the transfer slurry pool for storage and aging for later use;
[0148] The polycrystalline wear-resistant green body formula is composed of the following raw material components by weight: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, green body reinforcing agent 0.35%, debonding agent 1.1%;
[0149] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0150] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0151] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.4%, a Fe2O3 content of 0.6%, and a particle size D50 of 1.86 μm;
[0152] The chemical composition of the finely ground lithium tailings is composed of 17.83 wt% Al2O3, 69.11 wt% SiO2, 3.50 wt% K2O, 0.68 wt% Fe2O3, 3.45 wt% Na2O, 0.84 wt% CaO, 0.42 wt% MgO, 0.41 wt% Li2O, 0.18 wt% trace elements, and 3.58 wt% ignition loss. The trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel; the particle size D50 of the finely ground lithium tailings is 5.4 μm;
[0153] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0154] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, 105° volatile matter of 0.3%, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm.
[0155] (2) Preparation of high-transparency phenocryst green body formula slurry: The raw materials in the green body formula are mixed and ball-milled according to the proportion, and the high-transparency phenocryst green body formula slurry is obtained and then sent to the transfer slurry pool for storage and aging for later use;
[0156] The high-transparency phenocryst green body formula is composed of the following raw material components by weight percentage: 12% super white ball clay, 12% super white kaolin, 3% super white calcined talc, 4% high white bentonite, 20% high white sodium potassium stone, 15% glass powder, 17.3% super white lithium tailing powder, 15% barium carbonate, 0.6% green body reinforcing agent, and 1.1% debonding agent;
[0157] The high-transparency phenocryst blank formula consists of the following chemical components by weight: Al2O3 16.12 wt%, SiO2 57.82 wt%, K2O 1.78 wt%, Fe2O3 0.14 wt%, Na2O 3.97 wt%, CaO 0.25 wt%, MgO 1.25 wt%, BaO 11.69 wt%, and ignition loss 6.98 wt%;
[0158] The whiteness of the high-transmittance porphyroblast green body formula is 76%, and the transmittance is controlled to be 16.3%. The high-transmittance porphyroblast green body formula is processed by wet ball milling process, and the median diameter D50 of the mud is 9.3 μm.
[0159] The ball clay, high white kaolin, burned talc, bentonite, potassium sodium stone powder and finely ground lithium tailings are subjected to an iron removal process for three times to obtain raw materials of ultra-white ball clay with a whiteness of 72%; ultra-white kaolin with a whiteness of 74%; burned talc with a whiteness of 77%; ultra-white bentonite with a whiteness of 73%; ultra-white potassium sodium stone powder with a whiteness of 79% and ultra-white lithium tailings powder with a whiteness of 81%.
[0160] ⑶ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of ceramic colorant or emulsifier is added to the polycrystalline wear-resistant green body formula of step ⑴ and the high-transparency porphyroblast green body formula slurry of step ⑵, and after being stirred evenly, it is sent to a spray drying tower for powdering to obtain colored powder and stored for aging for later use;
[0161] The color powder is set to 8 kinds, and the specific settings are as follows:
[0162] The white powder is composed of the following components by weight percentage: 90wt% of polycrystalline wear-resistant blank formula slurry and 10wt% of emulsifier; wherein the emulsifier is composed of the following components by weight percentage: 20wt% of zirconium dioxide, 55wt% of zirconium silicate and 25wt% of titanium dioxide;
[0163] The light apricot color powder is composed of the following components by weight percentage: 100wt% of high-transparency phenocryst blank formula slurry;
[0164] The gray powder is composed of the following components by weight percentage: 99.7wt% of polycrystalline wear-resistant blank formula slurry, 0.2wt% of cobalt black material, and 0.1wt% of orange material;
[0165] The light green powder is composed of the following components by weight percentage: 99.8wt% of high-transparent phenocryst blank formula mud, 0.18wt% of apple green material, and 0.02wt% of chrome green material;
[0166] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry 98.8wt%, cobalt black material 1.1wt%, manganese red material 0.1wt%;
[0167] The brown powder is composed of the following components by weight percentage: 97.3wt% of polycrystalline wear-resistant blank formula slurry, 0.4wt% of cobalt black material, 0.7wt% of praseodymium yellow material, and 1.6wt% of manganese red material;
[0168] The light yellow powder is composed of the following components by weight percentage: 99.4wt% of high-transparent phenocryst blank formula mud, 0.4wt% of orange material, and 0.2wt% of praseodymium yellow material;
[0169] The red color powder is composed of the following components by weight percentage: 98.4wt% of polycrystalline wear-resistant blank formula slurry, 1.3wt% of manganese red material, and 0.3wt% of praseodymium yellow material;
[0170] The spray drying tower adopts a pressure spray drying system, which uses a nozzle plate with an aperture of 1.8 mm and an atomization pressure of 2.2 MPa. The particle size distribution of the obtained powder is as follows: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;
[0171] (4) Preparation of granular materials of different colors: The color powder of step (3) is granulated by a granulating device to obtain granular materials of different colors;
[0172] The color particle materials are provided in 5 kinds, specifically white particles, black particles, brown particles, light apricot particles, and light yellow particles;
[0173] The granulation equipment comprises five parts, namely, a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and can prepare particles with various effects, colors, thicknesses and specifications. The granulation equipment comprises a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads a total of five different color powders, namely, the white color powder, the black color powder, the brown color powder, the light apricot color powder and the light yellow color powder in step (3) on the surface of the conveyor belt in multiple layers according to design parameters, and the scraping device scrapes the powder at a fixed height according to the particle thickness requirement, and then presses the powder into blocks by the pressure roller, and finally conveys the powder to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage and standby;
[0174] The color particle material has a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a volume density of 1.61 g / cm 3 ;
[0175] (5) Preparation of mixed powder: uniformly mix the color powder of step (3) and the color granular material of step (4) according to the designed ratio to obtain a mixed powder for use;
[0176] The mixed powder is provided in 4 types according to the design requirements; specifically,
[0177] A mixed powder is composed of the following components by weight percentage: 10wt% white particles, 5wt% black particles, 30wt% light apricot powder, and 55wt% gray powder;
[0178] Mixed powder B is composed of the following components by weight percentage: 8wt% brown particles, 15wt% light yellow particles, 5wt% white particles, 3wt% black powder, and 69wt% gray powder;
[0179] Mixed powder C is composed of the following components by weight percentage: 5wt% brown particles, 20wt% light apricot particles, 10wt% white particles, 15wt% red powder, 40wt% grey powder, and 10wt% light green powder;
[0180] The D mixed powder is composed of the following components by weight percentage: 15wt% of light yellow powder, 35wt% of light apricot powder, 3wt% of black powder, and 47wt% of gray powder.
[0181] (6) Whole-body fabrication: The mixed powder material in step (5) is arranged in texture according to the design parameters through the whole-body fabrication forming system to obtain a blank layer with a phenocryst granite texture;
[0182] See also Figure 6 As shown, the whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform is composed of a fabric mechanism 11, a transition belt 12, a transition hopper 13, a grille 14, a transfer feeding hopper 15, and a movable feeding hopper 16. The fabric mechanism 11 is designed with 6 groups, which are arranged at the top of the whole body fabric platform 1. The fabric mechanism 11 forms a blank layer after fabricating according to the designed texture pattern. The blank layer is conveyed to the transition hopper 13 by the transition belt 12 and fixed by the grille 14, and then conveyed to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole body fabric platform 1 through the conveying mechanism 3. The movable feeding hopper 16 feeds the material and scrapes it flat, and then presses and forms the wear-resistant blank layer;
[0183] The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm;
[0184] (7) Pressing and molding: feeding the blank layer of step (6) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0185] The pressing pressure of the pressing molding is 45MPa / cm 3 , the wear-resistant green body layer has a thickness of 20 mm;
[0186] ⑻ Drying: The formed wear-resistant body layer is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0187] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0188] ⑼ Water spraying: spray water on the surface of the wear-resistant blank in step ⑻ to wet it;
[0189] ⑽Preparation of color slurry: Based on the formula of the polycrystalline wear-resistant matrix body in step ⑴ and the formula of the high-transparency porphyroblast body in step ⑵, introduce pigments and raw materials such as ceramic colorants and kaolin, and obtain color slurry through calcination, grinding, spray drying and other processing techniques;
[0190] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is 1.75g / cm 3 , 40° viscosity is 60mpa.s, D50 particle size is controlled to 12μm;
[0191] The color paste is provided in 8 types according to the design requirements, specifically including:
[0192] The color paste 1 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of cobalt blue colorant;
[0193] Color slurry 2 is composed of the following components by weight percentage: wear-resistant base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0194] Color slurry 3 is composed of the following components by weight percentage: wear-resistant base slurry 98wt%, brown colorant 2wt%;
[0195] The color paste 4 is composed of the following components by weight: 98wt% of high-transparency base paste and 2wt% of wrapped red material;
[0196] The color slurry 5 weight percent is composed of the following components: wear-resistant base slurry 97wt%, orange color material 3wt%;
[0197] The color paste 6 weight percent is composed of the following components: 97wt% of high-transparency base paste, 3wt% of wrapped yellow material;
[0198] The color paste 7 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of black colorant;
[0199] The color paste 8 is composed of the following components by weight percentage: 98wt% of high-transmittance paste and 2wt% of green colorant;
[0200] The wear-resistant basic slurry is composed of the following components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, green body reinforcing agent 0.35%, debonding agent 1.1%; after the formula is prepared by weight percentage, it is ball-milled into a basic slurry according to a wet process, and the slurry has a water content of 36%, a viscosity of 60mpa.s at 40°, and a D50 particle size of 4μm;
[0201] ⑾Spraying decoration: on the wetted surface of the blank, use the color slurry in step ⑽ to perform digital spraying decoration according to the designed pattern to form a decorative wear-resistant layer;
[0202] The decorative wear-resistant layer is formed by decorative spraying of 8 different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2mm. The thickness of the decorative wear-resistant layer is 0.8mm.
[0203] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0204] ⑿ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer of step ⑾ at a drying temperature of 150° C. for 8 minutes;
[0205] ⒀High temperature firing: sending the ceramic body of step ⑿ into a roller kiln for firing;
[0206] The high temperature firing has a firing temperature of 1220° C. and a firing time of 75 minutes. The water absorption rate of the fired product is 0.06%, and the Ra value of the product out of the kiln is 1.72 μm.
[0207] ⒁Processing: Polish and grind the edges of the fired semi-finished products to finally obtain polished, wear-resistant special granite ceramic finished tiles.
[0208] The processing is specifically to polish the product obtained in step ⒀ first and then grind the edges, wherein the polishing is polishing of the decorative wear-resistant surface; the polishing process parameters are: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive blocks are matched as follows: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and Ra value of the product after polishing is 0.052μm.
[0209] The difference between Comparative Example 2 and Example 1 is that the decorative wear-resistant layer formula material is not subjected to light firing processing and is directly prepared and used according to the blank formula.
[0210] Specifically, the methods of Example 1 and Comparative Example 2 were used to prepare wear-resistant special granite ceramic tiles, and the obtained ceramic tiles were tested for wear quality of 12,000 revolutions or flexural strength, water absorption, and Mohs hardness performance according to the national standard GB / T 4100-2015 for ceramic tiles. The results are shown in Table 2 below:
[0211] Table 2 Example 1 and Comparative Example 2
[0212]
[0213] The test results of Example 1 and Comparative Example 2 show that when the decorative wear-resistant layer formula material of the present invention is not subjected to light firing, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic tile will decrease. Figure 1 and Figure 3 The phase detection results show that Figure 1 The types and contents of crystal phases are higher than Figure 3 This is because during the light firing process, various materials in the formula undergo a solid-phase reaction, generating a portion of wear-resistant crystal phase in advance. At the same time, after the calcination process, the reaction activity of the formula raw materials is improved, which promotes the formation of crystal phase during the secondary firing, so the wear resistance of the product can be better improved.
[0214] Example 2
[0215] The wear-resistant special granite ceramic tile with phenocryst effect described in this embodiment mainly includes two parts: a wear-resistant body layer and a decorative wear-resistant layer. The main production process technology route is as follows:
[0216] ⑴ Preparation of polycrystalline wear-resistant matrix body formula slurry: The raw materials in the body formula are mixed and ball-milled according to the proportion, and the polycrystalline wear-resistant body formula slurry is sent to the transfer slurry pool for storage and aging for later use;
[0217] The polycrystalline wear-resistant green body formula is composed of the following raw material components by weight: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, green body reinforcing agent 0.35%, debonding agent 1.1%;
[0218] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0219] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0220] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.4%, a Fe2O3 content of 0.6%, and a particle size D50 of 1.86 μm;
[0221] The chemical composition of the finely ground lithium tailings is composed of 17.83 wt% Al2O3, 69.11 wt% SiO2, 3.50 wt% K2O, 0.68 wt% Fe2O3, 3.45 wt% Na2O, 0.84 wt% CaO, 0.42 wt% MgO, 0.41 wt% Li2O, 0.18 wt% trace elements, and 3.58 wt% ignition loss. The trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel; the particle size D50 of the finely ground lithium tailings is 5.4 μm;
[0222] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0223] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, 105° volatile matter of 0.3%, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm.
[0224] (2) Preparation of high-transparency phenocryst green body formula slurry: The raw materials in the green body formula are mixed and ball-milled according to the proportion, and the high-transparency phenocryst green body formula slurry is obtained and then sent to the transfer slurry pool for storage and aging for later use;
[0225] The high-transparency phenocryst green body formula is composed of the following raw material components by weight percentage: 12% super white ball clay, 12% super white kaolin, 3% super white calcined talc, 4% high white bentonite, 20% high white sodium potassium stone, 15% glass powder, 17.3% super white lithium tailing powder, 15% barium carbonate, 0.6% green body reinforcing agent, and 1.1% debonding agent;
[0226] The high-transparency phenocryst blank formula consists of the following chemical components by weight: Al2O3 16.12 wt%, SiO2 57.82 wt%, K2O 1.78 wt%, Fe2O3 0.14 wt%, Na2O 3.97 wt%, CaO 0.25 wt%, MgO 1.25 wt%, BaO 11.69 wt%, and ignition loss 6.98 wt%;
[0227] The whiteness of the high-transmittance porphyroblast green body formula is 76%, and the transmittance is controlled to be 16.3%. The high-transmittance porphyroblast green body formula is processed by wet ball milling process, and the median diameter D50 of the mud is 9.3 μm.
[0228] The ball clay, high white kaolin, burnt talc, bentonite, potassium sodium stone powder, and finely ground lithium tailings are subjected to an iron removal process to remove iron three times to obtain raw materials ultra-white ball clay with a whiteness of 72%; ultra-white kaolin with a whiteness of 74%; burnt talc with a whiteness of 77%; ultra-white bentonite with a whiteness of 73%; ultra-white potassium sodium stone powder with a whiteness of 79%; and ultra-white lithium tailings powder with a whiteness of 81%.
[0229] ⑶ Preparation of powders of different colors: according to the requirements of texture pattern design, a certain proportion of ceramic colorant or emulsifier is added to the polycrystalline wear-resistant green body formula of step ⑴ and the high-transparency porphyroblast green body formula slurry of step ⑵, and after being stirred evenly, it is sent to a spray drying tower for powdering to obtain colored powder and stored for aging for later use;
[0230] The color powder is set to 8 kinds, and the specific settings are as follows:
[0231] The white powder is composed of the following components by weight percentage: 90wt% of polycrystalline wear-resistant blank formula slurry and 10wt% of emulsifier; wherein the emulsifier is composed of the following components by weight percentage: 20wt% of zirconium dioxide, 55wt% of zirconium silicate and 25wt% of titanium dioxide;
[0232] The light apricot color powder is composed of the following components by weight percentage: 100wt% of high-transparency phenocryst blank formula slurry;
[0233] The gray powder is composed of the following components by weight percentage: 99.7wt% of polycrystalline wear-resistant blank formula slurry, 0.2wt% of cobalt black material, and 0.1wt% of orange material;
[0234] The light green powder is composed of the following components by weight percentage: 99.8wt% of high-transparent phenocryst blank formula mud, 0.18wt% of apple green material, and 0.02wt% of chrome green material;
[0235] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry 98.8wt%, cobalt black material 1.1wt%, manganese red material 0.1wt%;
[0236] The brown powder is composed of the following components by weight percentage: 97.3wt% of polycrystalline wear-resistant blank formula slurry, 0.4wt% of cobalt black material, 0.7wt% of praseodymium yellow material, and 1.6wt% of manganese red material;
[0237] The light yellow powder is composed of the following components by weight percentage: 99.4wt% of high-transparent phenocryst blank formula mud, 0.4wt% of orange material, and 0.2wt% of praseodymium yellow material;
[0238] The red color powder is composed of the following components by weight percentage: 98.4wt% of polycrystalline wear-resistant blank formula slurry, 1.3wt% of manganese red material, and 0.3wt% of praseodymium yellow material;
[0239] The spray drying tower adopts a pressure spray drying system, which uses a nozzle plate with an aperture of 1.8 mm and an atomization pressure of 2.2 MPa. The particle size distribution of the obtained powder is as follows: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;
[0240] (4) Preparation of granular materials of different colors: The color powder of step (3) is granulated by a granulating device to obtain granular materials of different colors;
[0241] The color particle materials are provided in 5 kinds, specifically white particles, black particles, brown particles, light apricot particles, and light yellow particles;
[0242] The granulation equipment comprises five parts, namely, a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and can prepare particles with various effects, colors, thicknesses and specifications. The granulation equipment comprises a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads a total of five different color powders, namely, the white powder, the black powder, the brown powder, the light apricot powder and the light yellow powder in step (3) on the surface of the conveyor belt in multiple layers according to design parameters, and the scraping device scrapes the powder at a fixed height according to the particle thickness requirement, and then presses the powder into blocks by the pressure roller, and finally conveys the powder to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage.
[0243] The color particle material has a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a volume density of 1.61 g / cm 3 .
[0244] (5) Preparation of mixed powder: uniformly mix the color powder of step (3) and the color granular material of step (4) according to the designed ratio to obtain a mixed powder for use;
[0245] The mixed powder is provided in 4 types according to the design requirements; specifically,
[0246] A mixed powder is composed of the following components by weight percentage: 10wt% white particles, 5wt% black particles, 30wt% light apricot powder, and 55wt% gray powder;
[0247] Mixed powder B is composed of the following components by weight percentage: 8wt% brown particles, 15wt% light yellow particles, 5wt% white particles, 3wt% black powder, and 69wt% gray powder;
[0248] Mixed powder C is composed of the following components by weight percentage: 5wt% brown particles, 20wt% light apricot particles, 10wt% white particles, 15wt% red powder, 40wt% grey powder, and 10wt% light green powder;
[0249] The D mixed powder is composed of the following components by weight percentage: 15wt% of light yellow powder, 35wt% of light apricot powder, 3wt% of black powder, and 47wt% of gray powder.
[0250] (6) Whole-body fabrication: The mixed powder material in step (5) is arranged in texture according to the design parameters through the whole-body fabrication forming system to obtain a blank layer with a phenocryst granite texture;
[0251] See also Figure 6 As shown, the whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform is composed of a fabric mechanism 11, a transition belt 12, a transition hopper 13, a grille 14, a transfer feeding hopper 15, and a movable feeding hopper 16. The fabric mechanism 11 is designed with 6 groups, which are arranged at the top of the whole body fabric platform 1. The fabric mechanism 11 forms a blank layer after fabricating according to the designed texture pattern. The blank layer is conveyed to the transition hopper 13 by the transition belt 12 and fixed by the grille 14, and then conveyed to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole body fabric platform 1 through the conveying mechanism 3. The movable feeding hopper 16 feeds the material and scrapes it flat, and then presses and forms the wear-resistant blank layer;
[0252] The blank layer is formed by a whole body cloth forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm.
[0253] (7) Pressing and molding: feeding the blank layer of step (6) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0254] The pressing pressure of the pressing molding is 45MPa / cm 3 The wear-resistant green body layer has a thickness of 20 mm.
[0255] ⑻ Drying: The formed wear-resistant body layer is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0256] The drying time is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0257] ⑼ Water spraying: spray water on the surface of the wear-resistant blank in step ⑻ to wet it;
[0258] ⑽Preparation of color slurry: Based on the formula of the polycrystalline wear-resistant matrix body in step ⑴ and the formula of the high-transparency porphyroblast body in step ⑵, introduce pigments and raw materials such as ceramic colorants and kaolin, and obtain color slurry through calcination, grinding, spray drying and other processing techniques;
[0259] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is 1.75g / cm 3 , 40° viscosity is 60mpa.s, D50 particle size is controlled to 12μm;
[0260] The color paste is provided in 8 types according to the design requirements, specifically including:
[0261] The color paste 1 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of cobalt blue colorant;
[0262] Color slurry 2 is composed of the following components by weight percentage: wear-resistant base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0263] Color slurry 3 is composed of the following components by weight percentage: wear-resistant base slurry 98wt%, brown colorant 2wt%;
[0264] The color paste 4 is composed of the following components by weight: 98wt% of high-transparency base paste and 2wt% of wrapped red material;
[0265] The color slurry 5 weight percent is composed of the following components: wear-resistant base slurry 97wt%, orange color material 3wt%;
[0266] The color paste 6 weight percent is composed of the following components: 97wt% of high-transparency base paste, 3wt% of wrapped yellow material;
[0267] The color paste 7 is composed of the following components by weight percentage: 99wt% of wear-resistant base paste and 1wt% of black colorant;
[0268] The color paste 8 is composed of the following components by weight percentage: 98wt% of high-transmittance paste and 2wt% of green colorant;
[0269] The wear-resistant base slurry is composed of the following components by weight percentage: 89.2% of light-burned wear-resistant material, 9.52% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0270] The formula composition of the lightly fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank in step (1), except that a lightly fired process is required; the lightly fired process is to prepare the formula according to the weight percentage, and then ball-mill it into a slurry according to a wet process, wherein the slurry has a moisture content of 36%, a viscosity of 60 mpa.s at 40°, and a D50 particle size of 4 μm; the ball-milled slurry is spray-dried to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material, and fired at a temperature of 1080° C. to obtain the lightly fired wear-resistant material;
[0271] The high-permeability base slurry is composed of the following components by weight percentage: 89.2% of light-burned high-permeability material, 9.52% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0272] The formula composition of the lightly fired high-permeability material is consistent with the formula of the high-transparency porphyroblast blank in step (2), the difference being that light firing is required; the light firing is to prepare the formula according to weight percentage, and then ball-mill it into slurry according to a wet process, with the slurry having a moisture content of 36%, a viscosity of 60 mpa.s at 40°, and a D50 particle size of 4 μm; the ball-milled slurry is spray-dried to obtain a powder, the obtained powder is loaded into a sagger made of refractory material, and fired at a temperature of 1050°C to obtain the lightly fired high-permeability material.
[0273] ⑾Spraying decoration: on the wetted surface of the blank, use the color slurry in step ⑽ to perform digital spraying decoration according to the designed pattern to form a decorative wear-resistant layer;
[0274] The decorative wear-resistant layer is formed by decorative spraying of 8 different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2mm. The thickness of the decorative wear-resistant layer is 0.8mm.
[0275] The digital spraying process is a process that uses digital information to directly control the printing, and the printing volume per square meter is 1400g.
[0276] ⑿ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer of step ⑾ at a drying temperature of 150° C. for 8 minutes;
[0277] ⒀High temperature firing: sending the ceramic body of step ⑿ into a roller kiln for firing;
[0278] The high temperature firing has a firing temperature of 1220° C. and a firing time of 75 minutes. The water absorption rate of the fired product is 0.06%, and the Ra value of the product out of the kiln is 1.72 μm.
[0279] ⒁Processing: The semi-finished products after firing are ground to obtain natural-surface wear-resistant special granite ceramic finished tiles.
[0280] The method of Example 2 was used to prepare the wear-resistant special granite ceramic tiles, and the obtained ceramic tiles and natural granite were tested for the wear depth, flexural strength, water absorption rate, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 3 below:
[0281] Table 3 Example 2 and natural granite
[0282]
[0283] It can be seen from the test results of Example 2 and natural granite that the granite ceramic tile prepared by the method of Example 2 has better wear resistance, Mohs hardness and flexural strength than natural granite. This is because the granite ceramic tile prepared by the method of Example 2 produces more high-hardness wear-resistant crystals, including mullite, corundum, zircon, quartz, rutile, anorthite, etc., where the Mohs hardness of mullite and anorthite reaches 6, rutile is 6 to 6.5, zircon is 7.5 to 8, and corundum is 9. These high-hardness wear-resistant crystals are not only of many types, but also of high content, thereby improving the wear resistance of the product.
[0284] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.
Claims
1. A method for preparing a wear-resistant special granite ceramic tile with phenocryst effect, characterized in that: The following steps are involved: ⑴ Preparation of polycrystalline wear-resistant matrix green body formula slurry: The raw materials in the polycrystalline wear-resistant matrix green body formula are mixed and ball-milled according to the proportion, and the polycrystalline wear-resistant green body formula slurry is obtained and then sent to the transfer slurry pool for storage and aging for standby use; (2) Preparation of high-transmittance phenocryst blank formula slurry: The raw materials in the high-transmittance phenocryst blank formula are mixed and ball-milled according to the proportion, and the high-transmittance phenocryst blank formula slurry is sent to the transfer slurry pool for storage and aging for later use; ⑶ Preparation of powders of different colors: according to the requirements of the texture pattern design, add a set ratio of ceramic colorant or emulsifier to the polycrystalline wear-resistant green body formula slurry in step ⑴ and the high-transparency porphyroblast green body formula slurry in step ⑵, stir evenly and send to a spray drying tower for powdering to obtain color powder and store it for aging for later use; (4) Preparation of granular materials of different colors: Part of the color powder of step (3) is granulated by a granulating device to obtain granular materials of different colors; (5) Preparation of mixed powder: uniformly mix the color powder of step (3) and the color granular material of step (4) according to the designed ratio to obtain a mixed powder for use; (6) Whole-body fabrication: The mixed powder material in step (5) is arranged in texture according to the design parameters through the whole-body fabrication forming system to obtain a blank layer with a phenocryst granite texture; (7) Pressing and molding: feeding the blank layer of step (6) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer; ⑻ Drying: The formed wear-resistant body layer is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa; ⑼ Water spraying: spray water on the surface of the wear-resistant blank in step ⑻ to wet it; ⑽Preparation of color slurry: Based on the formula of the polycrystalline wear-resistant matrix body in step ⑴ and the formula of the high-transparency porphyroblast body in step ⑵, ceramic colorant and kaolin are introduced, and the color slurry is obtained through calcination, grinding and spray drying. ⑾Spraying decoration: on the wetted surface of the blank, use the color slurry in step ⑽ to perform digital spraying decoration according to the designed pattern to form a decorative wear-resistant layer; ⑿ Drying of decorative wear-resistant layer: drying temperature is 100-200℃, drying time is 3-8min; ⒀High temperature firing: sending the ceramic body of step ⑿ into a roller kiln for firing; ⒁Processing: The fired semi-finished products are polished or not polished and ground, and finally the wear-resistant special granite ceramic finished tiles with polished, natural or special-shaped surfaces are obtained.
2. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: The polycrystalline wear-resistant green body formula in the step (1) is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, green body reinforcing agent 0 to 1%, and debonding agent 1 to 3%; The multi-crystalline wear-resistant blank formulation is composed of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 1-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%; In the step (1), the processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm.
3. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 2, characterized in that: The fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100%, a Fe2O3 content of 0-1%, and a particle size D50 < 3 μm; The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements 0-1wt%, ignition loss 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm; the trace elements include rubidium, gallium, strontium, cadmium, and nickel; The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm; The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96%, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.
4. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: The high-transparency phenocryst blank formula in step (2) is composed of the following raw material components by weight percentage: ultra-white ball clay 8%-15%, ultra-white kaolin 8%-15%, ultra-white burned talc 0%-5%, high-white bentonite 3-6%, high-white potassium sodium stone 15-25%, glass powder 10-20%, ultra-white lithium tailings powder 10%-20%, barium carbonate 10%-20%, blank reinforcing agent 0-1%, and debonding agent 1-3%; The high-transparency phenocryst blank formulation is composed of the following chemical components by weight percentage: Al2O3 15-20wt%, SiO2 60-70wt%, K2O 1-3wt%, Fe2O3 0-0.5wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, BaO 7-16wt%, loss on ignition 0-8wt%; In step (2), the whiteness of the high-transmittance porphyroblast blank formula is controlled to be 70-80%, the transmittance is controlled to be 10-20%, the high-transmittance porphyroblast blank formula is processed by wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm; The raw materials used in the high-transparency porphyroblastic body formula of step (2) are ultra-white ball clay, ultra-white kaolin, ultra-white burned talc, ultra-white bentonite, ultra-white lithium tailings powder, and high-white potassium sodium stone, which are obtained by removing iron from ball clay, high-white kaolin, burned talc, bentonite, potassium sodium stone powder, and finely ground lithium tailings. The raw materials are deironed 1 to 5 times, and the whiteness is controlled to be 70 to 80%.
5. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: The color powder in step (3) is composed of the following components by weight percentage: 0-100wt% of polycrystalline wear-resistant green body formula slurry, 0-100wt% of high-transparency porphyroblast green body formula slurry, 0-5wt% of ceramic colorant, and 0-10wt% of opacifier; the color powder is provided with 2-10 different types of colors; The ceramic colorant in step (3) is selected from the following: The invention is composed of the following components by weight percentage: cobalt blue: 0-100wt%, manganese red: 0-100wt%, apple green: 0-100wt%, chrome green: 0-100wt%, orange yellow: 0-100wt%, praseodymium yellow: 0-100wt%, cobalt black: 0-100wt%; The composition is composed of the following components by weight percentage: cobalt blue: 0-100wt%, vanadium zirconium blue: 0-100wt%, brown: 0-100wt%, package red: 0-100wt%, orange: 0-100wt%, package yellow: 0-100wt%, black: 0-100wt%, green: 0-100wt%; The opacifier in step (3) is composed of the following components by weight percentage: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%; Step (3) The spray drying tower adopts a pressure spray drying system, the spray drying system uses a nozzle sheet combination with an aperture of 1.5 mm to 2.0 mm, and the atomization pressure is 1.8 MPa to 2.6 MPa. The particle grading of the obtained powder is that the particles on the 20 mesh sieve account for less than 6%, the particles between 20 mesh and 40 mesh account for 20% to 25%, the particles between 40 mesh and 60 mesh account for 40% to 45%, the particles between 60 mesh and 80 mesh account for 15% to 20%, and the particles below 80 mesh account for less than 3%, and the specific gravity of the powder is 0.85 to 0.95 g / cm 3 , the moisture content is controlled at 6-8%, and the angle of repose is controlled at 33°-38°.
6. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: The granulation equipment in step (4) comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder in step (3) on the surface of the conveyor belt in multiple layers according to the design parameters, and the powder is scraped and flattened by the scraping device at a fixed height according to the particle thickness requirement, and then pressed into a block by the pressure roller, and finally transported to the cutter to be processed into color granular materials of different colors, sizes and shapes for storage and standby; the color granular materials are provided with 2 to 6 kinds, and the particle size is controlled to be 3 to 20 mm: the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥0.1 Mpa, and the volume density is controlled to be ≥1.0 g / cm 3 ; In step ⑸, the mixed powder is set to 2 to 6 types, and is composed of the following components by weight percentage: color powder: 0 to 100wt%, color granular material: 0 to 100wt%.
7. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: The whole body fabric forming system described in step (6) comprises a whole body fabric platform, a pressing and forming platform, and a conveying mechanism; the whole body fabric platform is composed of a fabric mechanism, a transition belt arranged at the bottom of the fabric mechanism, a transition hopper arranged at a position where the transition belt travels at a terminal lower than the transition belt, a grid connected to the bottom of the transition hopper, a movable feeding hopper arranged longitudinally above the conveying mechanism on the side of the pressing and forming platform, and a transfer feeding hopper; the fabric mechanism is designed in multiple groups and arranged at the top of the whole body fabric platform; The material distribution mechanism forms a blank layer after the material distribution is completed according to the designed texture pattern. The blank layer is transferred to the transition hopper by the transition belt, and is fixed by the grid and then sent to the mold cavity in the pressing and forming platform arranged at the tail end of the whole material distribution platform through the conveying mechanism. The material is fed by the movable feeding hopper and scraped flat, and then pressed and formed to obtain a wear-resistant blank layer. In step (6), the blank layer is formed by a whole-body fabric forming system to form a granite pattern texture that is consistent from bottom to top, and its thickness can be controlled to be 18 mm to 80 mm.
8. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: In step (7), the pressing pressure is > 40 MPa / cm 2 , the thickness of the wear-resistant green body layer is controlled to be 9mm-40mm; the drying time in step ⑻ is 50-120 minutes; the residual moisture of the green body after drying is ≤0.5%; the color slurry in step ⑽ is composed of the following components by weight percentage: 95-100% base slurry, 0-5% ceramic colorant, prepared by weight percentage, and ground into slurry using a wet ball milling process; the specific gravity of the color slurry is controlled to be 1.75±0.5g / cm 3 , 40° viscosity is 60~150mpa.s, D50 particle size is controlled to be 10μm~15μm; The basic slurry is composed of the following components by weight percentage: light-burned wear-resistant material: 0-90wt%, light-burned high-permeability material: 0-90wt%, kaolin: 8-20wt%, CMC: 0.2-1.0wt%, trimer: 0.5-1.0wt%, defoamer: 0.2-1.0wt%; The formula compositions of the lightly fired wear-resistant material and the lightly fired high-permeability material are respectively consistent with the formula of the polycrystalline wear-resistant blank in step (1) and the formula of the high-transparency porphyroblast blank in step (2), except that light firing is required; the light firing is to prepare the formula according to weight percentage, and then ball-mill it into slurry according to a wet process, wherein the slurry has a moisture content of 35-40%, a viscosity of 40-80 mpa.s at 40°, and a D50 particle size of 3μm-6μm; spray-dry the ball-milled slurry to obtain a powder, and the obtained powder is loaded into a sagger made of refractory material or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain the lightly fired wear-resistant material and the lightly fired high-permeability material.
9. The method for preparing the wear-resistant special granite ceramic tile with phenocryst effect according to claim 1, characterized in that: Step ⑾ The decorative wear-resistant layer is formed by CNC spraying process, using a variety of different color slurries for decorative printing according to the designed pattern texture. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, the pattern is narrowed by 0.2mm to 0.4mm, and the thickness of the decorative wear-resistant layer is 0 to 1mm; The digital spraying process in step ⑾ is a process of directly controlling the printing by using digital information, which can realize the printing of 4 to 10 different color slurries at the same time, and the printing amount per square meter is controlled to be 0 to 1800g; The high temperature firing described in step (9) is performed at a firing temperature of 1180-1250°C for 60-120 minutes. The water absorption rate of the fired product is ≤0.5%, and the Ra value of the product out of the kiln refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3 μm. The processing in step ⒁ includes two situations. The first situation is to directly grind the edge of the product after sintering in step ⒀; the second situation is to first polish the product obtained in step ⒀ and then grind the edge; The polishing is the polishing of the wear-resistant surface: the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
10. A wear-resistant special granite ceramic tile with phenocryst effect throughout the body, prepared by the preparation method according to any one of claims 1 to 9.
11. A polycrystalline wear-resistant body of a special granite ceramic tile with a phenocryst effect, characterized in that: The polycrystalline wear-resistant blank is formulated by the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burnt talc 0% to 5%, bentonite 3% to 6%, potassium sodium stone powder 15% to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, blank reinforcing agent 0% to 1%, and debonding agent 1% to 3%; The multi-crystalline wear-resistant blank formula consists of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 1-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%.
12. A high-transmittance phenocrystal body of a wear-resistant special granite ceramic tile with phenocrystal effect, characterized in that: The high-transparency phenocryst blank formula is composed of the following raw material components by weight percentage: 8% to 15% of super white ball clay, 8% to 15% of super white kaolin, 0% to 5% of super white calcined talc, 3% to 6% of high white bentonite, 15% to 25% of high white sodium potassium stone, 10% to 20% of glass powder, 10% to 20% of super white lithium tailing powder, 10% to 20% of barium carbonate, 0% to 1% of blank reinforcing agent, and 1% to 3% of debonding agent; The formula of the high-transparent phenocryst green body consists of the following chemical components by weight percentage: Al2O3 15-20wt%, SiO2 60-70wt%, K2O 1-3wt%, Fe2O3 0-0.5wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, BaO 7-16wt%, and ignition loss 0-8wt%.
Citation Information
Patent Citations
Preparation process and production system of natural-texture-imitated landscape brick
CN110883909A
Thin ceramic rock plate and preparation method thereof
CN111470856A
High-temperature daily porcelain body with weathered granite chinastone as raw material and manufacturing method of porcelain product of high-temperature daily porcelain body
CN111848146A
Granite ceramic tile with natural stone texture and manufacturing method thereof
CN112645715A
Large-particle full-body rock plate, preparation method and rolling granulator
CN114195479A